Development and feasibility of a virtual reality-based exergaming program to enhance cardiopulmonary fitness in children with developmental coordination disorder - Ju, Ya-Ju; Du, Yi-Chun; Huang, Hsien-Chun; Hu Kao, Po-Sen; Cherng, Rong-Ju (Frontiers in Pediatrics, 2023)
Developmental coordination disorder (DCD) is a neurodevelopmental disorder characterized by motor skill deficits. Such deficits often limit children's participation in physical activities, further affecting their overall health, including through reduced cardiopulmonary fitness. Because virtual reality (VR) devices offer interactive games and activities that require various movements and coordination, they can serve as motivating and enjoyable means for children to perform physical exercise. In this study, we developed a VR-based exergaming system and tested its ability to enhance the cardiopulmonary fitness of children with DCD.Thirteen children with DCD and 10 young adults were recruited in phase I to examine the test-retest reliability and concurrent validity of our system (including a custom-made heart rate monitor) with a commercial heart rate device. In phase II, we included an additional 13 children with DCD to test the feasibility of the system. We tested the outcomes using the enjoyment rating scale, intrinsic motivation inventory (IMI), and 20-m shuttle run test (20mSRT).In phase I, test-retest reliability was good to excellent in the static task and moderate to good in the dynamic task. Concurrent validity was excellent in both tasks. In phase II, more than half of the children (18 out of 26) assigned the maximum rating for their enjoyment of the game; they also had high average scores on the IMI. Furthermore, after the 8-week training using the VR program, the average of the running distance of the 26 children in the 20mSRT had increased significantly from 129.23 m to 176.92 m (p < 0.001).Our VR-based exergaming program can serve as an alternative intervention for enhancing cardiopulmonary fitness in children with DCD.